A multimedia database server for an integrated radiology information system. - Vital, Dominique. (University of Ottawa (Canada), 1990)
The need for a computer-based information management system in a department of radiology is not new. For more than ten years now, it has been addressed by a variety of systems which all offer but partial solutions to the problem: Radiology Information System (RIS) for factual data, Picture Archiving and Communication System (PACS) for radiological images, voice-messaging system for verbal reports, etc. A multimedia information system is therefore required to integrate and expand the capabilities of each of these partial solutions. In this thesis, we investigate the information management aspects of such a multimedia information system. We characterize the radiological information, by identifying its components and their dynamic evolution. Based on this characterization, we apply concepts developed for the automated office environment to our system design: databases, ISO client-server architecture and ISO multimedia document architecture. As well, our system design includes the major achievements of PACS technology for radiological images storage and transfer. From all these, we elaborate a set of requirements for an information management system, and specify the functional architecture of a system which will meet these requirements. We also develop an appropriate data model for radiological information. Finally, we present a prototype implementing our system's specifications for textual and image data.
Keywords: Engineering, Electronics and Electrical.